2014
DOI: 10.1007/s00429-014-0764-2
|View full text |Cite
|
Sign up to set email alerts
|

Y-P30 promotes axonal growth by stabilizing growth cones

Abstract: The 30-amino acid peptide Y-P30, generated from the N-terminus of the human dermcidin precursor protein, has been found to promote neuronal survival, cell migration and neurite outgrowth by enhancing the interaction of pleiotrophin and syndecan-3. We now show that Y-P30 activates Src kinase and extracellular signal-regulated kinase (ERK). Y-P30 promotes axonal growth of mouse embryonic stem cell-derived neurons, embryonic mouse spinal cord motoneurons, perinatal rat retinal neurons, and rat cortical neurons. Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…Several cellular signals have been reported to be involved in the regulation of neuronal morphology, such as extracellular signal-regulated kinase (ERK) and Growth Associated Protein 43(GAP-43) 15. We examined the expression profiling of two critical proteins, ERK and GAP-43, in miR-196a transgenic mice, and the expression levels were significantly increased in miR-196a transgenic mice (Supplementary Figure 2A and 2B), suggesting miR-196a could enhance neuronal morphology via increases in ERK and GAP43 signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Several cellular signals have been reported to be involved in the regulation of neuronal morphology, such as extracellular signal-regulated kinase (ERK) and Growth Associated Protein 43(GAP-43) 15. We examined the expression profiling of two critical proteins, ERK and GAP-43, in miR-196a transgenic mice, and the expression levels were significantly increased in miR-196a transgenic mice (Supplementary Figure 2A and 2B), suggesting miR-196a could enhance neuronal morphology via increases in ERK and GAP43 signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Y-P30 is a ligand which enhances the interaction of the neurite growth-promoting matrix protein pleiotrophin and membrane-bound syndecan-2 and syndecan-3 [11]. Syndecan-3 is enriched on axons, and Y-P30 has been shown to promote axonal growth in a syndecan-3-dependent and heparan-sufate side chain-dependent manner in cortical stem cell-derived neurons, and in days-in-vitro (DIV) 3–4 retinal and cortical microexplants [1113]. In immature neurons, ligand binding to syndecans, including that of Y-P30, activates Y418 c-Src phosphorylation and evokes a Src-dependent activation of p42/44 ERK kinase [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Syndecan-3 is enriched on axons, and Y-P30 has been shown to promote axonal growth in a syndecan-3-dependent and heparan-sufate side chain-dependent manner in cortical stem cell-derived neurons, and in days-in-vitro (DIV) 3–4 retinal and cortical microexplants [1113]. In immature neurons, ligand binding to syndecans, including that of Y-P30, activates Y418 c-Src phosphorylation and evokes a Src-dependent activation of p42/44 ERK kinase [13, 14]. Y-P30 increases the levels of active Src kinase and F-actin in cortical axonal growth cones, leading to their stabilization against collapse-inducing semaphorin-3a [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of upregulated proteins in Paper II that indicate neuroprotective function is transthyretin in the PHZ and dermcidin in the SNX. Previous preclinical studies have shown transthyretin to be neuroprotective following ICH (295)(296)(297)(298) and dermcidin to be protective against oxidative damage in in vitro and in animal models (299)(300)(301)(302). The role of such proteins in the pathophysiology of ICH needs to be further explored in future research.…”
Section: Figure 61 Protein Increase Mechanismsmentioning
confidence: 99%